Spinal Anesthesia in Caesarean Section with Ovarian Cyst Permagna with Meigs Syndrome - Aulia Iqbal; Susi Sembiring (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2022)
Background: The ovarian cyst is the very common cyst intra-abdominal in the ovary. If it need termination, the common procedure is cesarean section then the best anesthesia technique that suitable is spinal anesthesia. The Meigs Syndrome is an uncommon clinical condition, in which benign ovarian tumors are usually accompanied by ascites and pleural effusion. About 1% of ovarian tumors can indicate Meigs syndrome. Meigs Syndrome case have been reported in woman before 30 years old.Case Illustration: We reported an evaluation of a 29 years old woman, Gestational 1 Partus 3 Abortus 0, 60 kg weight and 165 cm height came to hospital with enlargement of abdomen since 3 months ago. There wasn’t history of bleeding and fluid discharged from genital. There’s no complaint in urination and defecation. The patient has felt an enlarged abdomen since the age of 7 months of pregnancy during antenatal care to a obstetrician. The patient hemodynamic and vital signs are stable and the pregnancy already in 37-38th week. Based on that the obstetrician decided to terminate the pregnancy, we choose to do spinal anesthesia in the cesarean section because it’s easy, common, and best technique for short surgical procedures.Conclusion: In patient with Ovarian Cysts Permagna with Meigs Syndrome in Pregnancy, we need to understand the risk of complication of ovarian cyst is higher in the prenatal period than after birth. The diagnosis of fetal ovarian cyst should not affect the schedule and method of delivery. The management of Meigs Syndrome in Pregnancy this time we terminate the pregnancy because it’s already in 37-38th week, the spinal anesthesia management is nothing different with the normal pregnancy.